Cranial anatomy of the giant Middle Triassic temnospondyl Cherninia megarhina and a review of feeding in mastodonsaurids - Damiani, Ross J (Bernard Price Institute for Palaeontological Research, 2001)
The skull of Cherninia (,Parotosuchus') megarhina, a giant but poorly known mastodonsaurid temnospondyl from the Upper Horizon of the Middle Triassic N'tawere Formation of the Upper Luangwa Valley, Zambia, is redescribed and refigured in detail for the first time. Cherninia megarhina is highly derived in most aspects of its cranial morphology and is characterised by the presence of a massively broad and elongated snout, relatively tiny orbits that are set well back on the skull roof, small, near-laterally directed tabular horns, an occipital sensory sulcus, and prominent, forked ridges on the skull roof. The palate is characterised by the presence of a ventral exoccipital-pterygoid contact, a short basicranial suture, a narrow parasphenoid body, a broad pterygoid body, and choanae that are placed far forward of the interpterygoid vacuities. The presence in Cherninia megarhina of numerous cranial autapomorphies justifies its separation from Parotosuchus. These autapomorphies are shared with Cherninia (‘Parotosuchus') denwaifrom the Middle Triassic Denwa Formation of India. The lateral orientation of the tabular horns and morphology of the otic region suggests that Cherninia megarhina is slightly more derived than the Indian species. Mastodonsaurids have traditionally been perceived as passive, benthic suction-feeders. However, recent work on the anatomy and functional morphology of the skeleton of mastodonsaurids suggests that they were designed for active swimming and predation. As such, it is hypothesised that prey capture was achieved using sideways sweeps of the head rather than suction-feeding.
Keywords: temnospondyl; Triassic; Cherninia megarhina; Mastodonsauridae; feeding